Negotiating the value of "corporations' capital" in Norwegian Early Childhood Education and Care provision - Anne Sigrid Haugset (Taylor & Francis Group, 2021)
In this article I investigate how corporate Early Childhood Education and Care (ECEC) providers negotiate their position by contributing to a national ECEC policy development process. I discuss how their political engagement connects to changes in the institutional arrangements of the ECEC sector. The ECEC provider corporations' written responses to a policy consulting process are obtained and analyzed in light of Bourdieu-inspired theories of institutonalized organizational fields. The proposed new regulations are both countered and reframed in their responses. Providers with corporate organizational structures in unison call for for firmer national guidelines on ECEC centre quality and funding. I interpret their responses as attempts to increase the relevance of 'corporations' capital' over the raditional, local network embedded capital forms in quality ECEC provision. At this juncture, the corporate providers failed to shift competence from municipalities to national ECEC authorities The following parliamentary debate illuminates how non-profit provision in corporate organizational structures may appeal to left-wing parties rejecting commercial welfare provisions. A subgroup of for-profit corporate providers emphasizes sector cost-efficiency, connecting strongly to right-wing politicians' ambitions to limit public spending. Corporate providers hence represent an impetus for institutional change, able to build allies across the whole left-right spectre of politics.